The Family Support and Provider Support to Increase Exclusive Breastfeeding Coverage - Shinta Kristianti; Susanti Pratamaningtyas (Humanistic Network for Science and Technology (HNST), 2018)
Given that infant mortality rate in Indonesia is still high, especially in Kediri of up to seven cases per thousand live births, immediate breastfeeding is tremendously important for neonates. Relationships are very central to exclusive breastfeeding, breast milk as the only neonate intakes, at organizational and family level. Support from the mother's network of relatives, friends, and healthcare provider is likely to be important for breastfeeding success. This study seeks to determine the relational supports of family and healthcare provider with exclusive breastfeeding. The corelational analytic design using cross sectional approach was opted involving the population of all mothers with babies aged 6-7 months in Puskesmas (community health center) Plosoklaten Kediri, 46 mothers with babies aged 6-7 months were taken as the samples using simple random sampling. Chi Square test was used to see the strength of relationship between supports of family and healthcare provider and the exclusive breastfeeding. The correlation between family support and exclusive breastfeeding based on Chi Square statistic test result was p-value= 0.809 (there was no relationship between family support and exclusive breastfeeding). While the relationship between provider support and exclusive breastfeeding was p-value= 0.266 (there was no relation between the provider support and exclusive breastfeeding). Keywords: Family support, Provider support, Exclusive breastfeeding